Blood concentrations of remifentanil during and after infusion in horses anesthetized with isoflurane and dexmedetomidine. (August 2016) - Benmansour, Perrine; Billinsky, Jennifer; Duke-Novakovski, Tanya; Alcorn, Jane
Abstract: Objective: To determine blood remifentanil concentration in isoflurane-anesthetized horses during and after a 1 h remifentanil and dexmedetomidine infusion. Study design: Prospective study. Animals: Six adult mixed breed horses with (mean ± SD) bodyweight of 507 ± 61 kg and 14 ± 4 years of age. Methods: Following sedation with xylazine IV, anesthesia was induced with ketamine IV mixed with diazepam IV. Anesthesia was maintained with isoflurane in oxygen. After 52 ± 7 min for instrumentation, dexmedetomidine (0.25 μg kg − 1 followed by 1.0 μg − 1 kg − 1 h − 1 ) and remifentanil infusions (6 μg kg − 1 h − 1 ) were administered for a minimum of 60 min and horses recovered from anesthesia. Drug infusions were administered into the left jugular vein. Blood was sampled (4 mL) from the right jugular vein at predefined intervals before and during administration of remifentanil infusion. Following catheter flush, blood was sampled from the left jugular vein after the infusion was terminated while the horse was recovering from anesthesia. Blood was placed into tubes containing sodium heparin with citric acid, flash frozen in liquid nitrogen, and stored at − 80 °C until analysis. Blood remifentanil concentration was measured using high performance liquid chromatography and tandem mass spectrometry. Results: Mean peak remifentanil concentration was 7.14 ηg mL − 1 at 50 min after start of infusion. Mean volume of distribution was 268 ± 40 mL kg − 1 and mean half-life was 12.8 min. Blood concentration decreased to 1 ηg mL − 1 27 min after termination of infusion. Limit of quantification was 0.2 ηg mL − 1 . Highlights: Remifentanil infusion in anesthetized horses produces a peak blood concentration 50 minutes after start of infusion, and has a rapid clearance from the blood following termination of infusion.